Endoscopic ultrasonography guided cutting scar of esophageal stricture after endoscopic injection sclerotherapy - Fulong Zhang; Jing Xu; Yuandong Zhu; Yan Shi; Bo Wu; Hai Wang; Chaojun Huang (BMC Gastroenterology, 2022)
Abstract Objective To investigate efficacy and safety of endoscopic ultrasonography (EUS) guiding to cut the scar of esophageal stricture after endoscopic injection sclerotherapy (EIS). Methods The data of 10 patients with oesophageal stricture after esophageal varices EIS in our hospital from September 1, 2021 to December 31, 2021 treated by cutting the scar guided by ultrasonic endoscopy were retrospective, and the efficacy was evaluated. Results The dysphagia was obviously relieved in 9 patients during follow-up, and 1 patient suffered dysphagia again after the treatment. There was no complications of perforation, bleeding and infection among the paitents. Conclusion EUS guiding to cut the scar of esophageal stricture after EIS was safe and reliable.